Over-the-Counter Medicine Utilization by Beneficiaries Under Medical Schemes in South Africa - Padayachee, N (Drug Healthc Patient Saf, 2020)
BACKGROUND: South African medical insurance schemes (known as medical schemes) cover about 17% of the population. Within these schemes, access to medicines for a defined set of chronic diseases is mandated by legislation. However, much of the responsibility for treatment of minor conditions with non-prescription over-the-counter (OTC) medicines has been transferred to the individuals within the medical schemes. The overall expenditure on pharmacist-assisted therapy (PAT)/OTC medicines in South Africa is considerable and medical schemes endeavor to limit amounts paid out by devising strategies that will limit their financial exposure. AIM: To investigate how benefit design and other factors within two medical schemes influenced access to and payment for OTC medicines and to explore whether access to OTC medicines by individuals impacted on utilization of other health-care services. METHODS: Medical scheme data were obtained from a leading administrator for two health plans: one with comprehensive benefits covering 4593 beneficiaries (designated HI) and the other with lower benefits covering 54,374 beneficiaries (LO). Extracted data included beneficiary demographics, OTC medicines prescribed by doctors and/or dispensed by pharmacists, and monetary amounts claimed by individuals and paid by the medical schemes. Doctor consultations, costs and payments were also extracted, as were beneficiaries’ records of their chronic disease(s) and any episode(s) requiring hospitalization. RESULTS: Some 60–70% of beneficiaries submitted claims for OTC medicines accessed directly or recommended by a pharmacist, and 80–90% claimed OTC medicines that were prescribed by a doctor during a consultation. Amounts claimed and percentages of original products prescribed were substantially higher when accessed directly by beneficiaries or recommended by pharmacists than when doctors prescribed the medicines. In multivariate analysis, there was no clear advantage of offering access to OTC medicines in order to reduce visits to general practitioners, although in the LO plan it appeared that beneficiaries with chronic diseases made less use of the OTC benefit and more use of medical specialists. CONCLUSION: Within these two plans, there were higher costs and greater use of original products when beneficiaries or pharmacies accessed OTC medicines than when these medicines were prescribed by doctors. A key question is whether access to these medicines and the costs thereof would be managed better if paid for directly by individuals and not as insured benefits through the medical scheme.